2019
DOI: 10.15288/jsad.2019.80.252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alcohol Intoxication on Bystander Intervention in a Vignette Depiction of Sexual Assault

Abstract: Alcohol-related sexual violence remains a public health problem. Despite the popularity of sexual assault bystander intervention programs, these may be limited in addressing bystander intoxication because the effects of intoxication on intervening in a sexual assault are unknown. Therefore, we tested the effects of alcohol intoxication on the five steps of bystander intervention in a sexual assault vignette. Method: Young adults (N = 128; 50% women) were randomly assigned to consume alcohol (target blood alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 43 publications
5
52
1
1
Order By: Relevance
“…Furthermore, the vignette described the victim and perpetrator as friends of the bystander (participant), highlighting perhaps the sense of risk participants felt. Nevertheless, as Ham and colleagues (2019) reported, alcohol did affect risk detection and findings suggest that bystanders can be impaired in their ability to serve as capable guardians when they are intoxicated. Bystander intervention programs may want to consider encouraging a “sober bystander” approach to group outings, much as drinking and driving campaigns have emphasized the importance of a “designated driver” as one component to prevent motor vehicle accidents (Centers for Disease Control and Prevention [CDC], 1999).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Furthermore, the vignette described the victim and perpetrator as friends of the bystander (participant), highlighting perhaps the sense of risk participants felt. Nevertheless, as Ham and colleagues (2019) reported, alcohol did affect risk detection and findings suggest that bystanders can be impaired in their ability to serve as capable guardians when they are intoxicated. Bystander intervention programs may want to consider encouraging a “sober bystander” approach to group outings, much as drinking and driving campaigns have emphasized the importance of a “designated driver” as one component to prevent motor vehicle accidents (Centers for Disease Control and Prevention [CDC], 1999).…”
Section: Discussionmentioning
confidence: 80%
“…The one study that directly investigated this relationship suggests that alcohol impedes bystander intervention through reduced risk detection. Ham and colleagues (2019) found that acute alcohol intoxication reduces Steps a (noticing the event) and b (appraising it as dangerous) of the bystander model, and that Step b mediates the relation between alcohol intoxication and later stages of bystander assistance. We thus hypothesized:…”
Section: Barriers To Risk Appraisalmentioning
confidence: 92%
See 2 more Smart Citations
“…Findings suggest that some assault types (i.e., IKAD, UTSP) may be more amenable to traditional bystander interventions, as they are characterized by others being present immediately prior to the assault who could potentially intervene. Despite this necessary ingredient, IKAD and UTSP assaults in this sample were both more common when the participant had been using substances; thus, there may be concerns about whether intoxicated bystanders in these environments are able to detect sexual assault or its warning signs and subsequently intervene (Ham et al, 2019). Among those who described VCPP as the most significant incident, very few participants reported the presence of others around beforehand to intervene.…”
Section: Discussionmentioning
confidence: 99%